History of the Great Lakes Charting Advisers (Cooperative Charting by Canada and the United States) - Monteith, W. J.; Kerr, A. J.; Pittman, A. (The International Hydrographic Review, 2015)
Canada and the United States, recognizing the need to achieve compatibility in the marine charts produced along their boundary waters, have been cooperating during several decades in exchanging navigational information and working towards common charting standards. The mechanism for effecting these cooperative charting efforts has been the Great Lakes Charting Advisers. Standardization is one of the main aims of most maritime countries involved in the production of marine navigational charts, through their membership in the International Hydrographic Organization. The efforts of Canada and the United States are intended to complement the work of the International Hydrographic Organization in this regard and, in particular, the work of the North Sea International Chart Commission in its preparation of international specifications. The main purpose of this total effort is to provide the marine community with navigation documents that have been prepared to internationally agreed standards. The aim of this paper is to describe the international efforts of Canada and the United States in achieving these goals.